2013
DOI: 10.1016/j.celrep.2013.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Jagged-1 Is Necessary for Homeostatic and Regenerative Hematopoiesis

Abstract: Summary The bone marrow (BM) microenvironment is composed of multiple niche cells that, by producing angiocrine factors, maintain and regenerate the hematopoietic stem cell (HSC) pool (Morrison and Spradling, 2008). We have previously demonstrated that endothelial cells support the proper regeneration of the hematopoietic system following myeloablation (Butler et al., 2010; Hooper et al., 2009; Kobayashi et al., 2010). Here, we demonstrate that expression of the angiocrine factor Jagged-1, supplied by the BM v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
216
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 225 publications
(223 citation statements)
references
References 52 publications
3
216
0
Order By: Relevance
“…ECs form putative "vascular niches" that influence HSC development and maintenance, from the first definitive HSCs that emerge from the ventral wall of the dorsal aorta (6) to the ECs in the BM microenvironment that produce prohematopoietic Notch ligand jagged-1 (JAG1), which is required for homeostatic and regenerative hematopoiesis (14). Rafii et al showed that transduction of vascular endothelium with the E4ORF1 gene, which activates the Akt pathway in human ECs, augments human long-term MPP (LT-MPP) expansion through paracrine cues along key signaling pathways, including the Notch pathway (12,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…ECs form putative "vascular niches" that influence HSC development and maintenance, from the first definitive HSCs that emerge from the ventral wall of the dorsal aorta (6) to the ECs in the BM microenvironment that produce prohematopoietic Notch ligand jagged-1 (JAG1), which is required for homeostatic and regenerative hematopoiesis (14). Rafii et al showed that transduction of vascular endothelium with the E4ORF1 gene, which activates the Akt pathway in human ECs, augments human long-term MPP (LT-MPP) expansion through paracrine cues along key signaling pathways, including the Notch pathway (12,15,16).…”
Section: Introductionmentioning
confidence: 99%
“…The VEGF2 and VE-cadherin-dependent signaling pathways play an important role in these processes [177]. Thus the fact that endothelial cells promote HSCs self-renewal was also proved in the experiments with Jagged-1 deletion using VE-cadherin-Cre when perivascular cells, including the PDGFRa + CD51 + MSCs, remained unchanged either quantitatively or functionally [178]. At the same time other authors demonstrated that CD31 hi endomucin hi -endothelial cells modulate neoangiogenesis indirectly via the Notch-signaling in the perivascular progenitors [179,180].…”
Section: Endothelial Cellsmentioning
confidence: 89%
“…Inhibition of the Notch signal in the HSCs leads to their accelerated differentiation in vitro and depletion in vivo. From this it follows that Notch-signal is crucially important in HSCs maintenance in the undifferentiated state [230], and that canonical Notch-pathway promotes HSCs self-renewal and maintenance [178].…”
Section: Notchmentioning
confidence: 99%
“…HSCs reside in a specialized BME, which provides factors and signals necessary for HSC maintenance. Several cell types that form an integral part of the HSC BME have been identified, including cells of the osteoblast lineage, endothelial cells, and perivascular cells (13)(14)(15)(16)(17). In addition to HSC maintenance, populations of maturing hematopoietic cells have been revealed to develop within specialized BMEs, such as B lymphopoiesis (18).…”
mentioning
confidence: 99%